Blockchain Tech System: Optimization of the Use and Audit of Village Funds - Firmanto, Yuki; Widiarti, Nada Fajar Nurmani'ah (Journal of International Conference Proceedings, 2023)
The central government has moved to provide capital support in the form of village funds to every administrative area in Indonesia. According to ICW (2022), the entire budget allotted for village funding in 2022 will be IDR 68 trillion. According to Indonesia Corruption Watch (ICW) monitoring data from 2015 to 2022, there were 155 instances of village fund corruption, which caused state losses totaling IDR 381,947,508,605 (ICW, 2022). Village monies were deposited in regional accounts as a result of issues with village fund realization reports. By ensuring that village funds have a reporting system that adheres to the value for money standards, village funds will be spent as efficiently as possible. Qualitative descriptive writing is the style used. The blockchain that is being used has a transaction database as well as superior features like smart contracts and full information sharing between peers and outside, which can make it simpler for auditors to examine village money. In addition, this technology provides superior data distribution and security capabilities. Budget realization reports are made immediately by an accounting information system using data from a transaction database. The ideal usage and management of local funds are encouraged by this technology, it is hoped.